فاعلية برنامج إرشادي معرفي سلوكي لتنمية الصمود النفسي وخفض الألكسيثيميا لدى طالبات المرحلة الجامعية - محمد، أمل أحمد جمعة (رابطة التربويين العرب, 2019)
the study aims at preparing a standardized toot that suits the nature of the Arabian girl to measure both psychological resilience and alexithymia variables, besides reveling the nature of the relationship between both psychological resilience and Alexithymia and testing the effectiveness of cognitive behavioral program to develop the level of psychological resilience and to reduce Alexithymia level among the members of the experimental group; students of the Faculty of Education. The results revealed a negative correlative relationship between alexithymia and the overall degree of psychological resilience. It recorded the highest inverse correlation ratio between Alexithymia and emotional regulation dimension, followed by constructive social relations dimension, afterward holding responsibility dimension, next positive outlook on life and then the positive competency for change. However, no relationship was found between Alexithymia and solving problems dimension. There were also statistically significant differences at the level of 0.01 among the means of experimental group members arranged scores concerning psychological resilience and Alexithymia dimensions between the pre-application and post application in favor of the post application. This indicates the effectiveness of the indicative program with no significant differences between the means of the experimental group members arranged scores in both post and follow up test on the scale of psychological resilience and Alexithymia.
تهدف الدراسة إلى إعداد أداه مقننة تناسب طبيعة الفتاه العربية لقياس متغيري الصمود النفسي والالكسيثيميا، وكذلك الكشف عن طبيعة العلاقة بين الصمود النفسي والالكسيثيميا، واختبار فاعلية برنامج معرفي سلوكي لتنمية مستوى الصمود النفسي وخفض مستوى الالكسيثيميا لدى أفراد المجموعة التجريبية من طالبات كلية التربية جامعة بيشة، وأسفرت النتائج عن وجود علاقة ارتباطية سالبة بين الالكسيثيميا والدرجة الكلية للصمود النفسي، فقد سجلت اعلي نسبة ارتباط عكسي بين الالكسيثيميا وبعد تنظيم الانفعالات يليه بعد العلاقات الاجتماعية البناءة، ثم بعد تحمل المسئولية يليه النظرة الإيجابية للحياة ثم الكفاءة الإيجابية للتغيير، بينما لم يتم الاستدلال على وجود علاقة بين الالكسيثيميا وبعد حل المشكلات، وكذلك وجود فروق دالة إحصائيا عند مستوي 0.01 بين متوسطات رتب درجات أفراد المجموعة التجريبية على متغيري الصمود النفسي والالكسيثيميا بين التطبيقين القبلي والبعدي لصالح التطبيق البعدي، مما دل على فاعلية البرنامج الإرشادي، مع عدم وجود فروق داله بين متوسطات رتب درجات أفراد المجموعة التجريبية في القياسين البعدي والتتبعى على مقياسي الصمود والالكسيثيميا.
Keywords: طلبة الجامعة -- الألكسيثيميا -- الصمود النفسي -- الإرشاد المعرفي السلوكي -- البرامج الإرشادية -- كلية التربية -- جامعة بيشة